Absorption of red clover isoflavones in human subjects: results from a pilot study - Maul, Ronald; Kulling, Sabine E. (British journal of nutrition, 2010)
In addition to soya-derived preparations, red clover-based dietary supplements have gained considerable interest as an alternative isoflavone (IF) source. While metabolism and bioavailability of the main IF from both sources have already been investigated, studies are still lacking on the biokinetic behaviour of IF, which are present in red clover in minor amounts. In the present pilot study, in which seven volunteers ingested a single dose of a commercial red clover dietary supplement, we focused on the absorption of three such IF, irilone (IRI), prunetin (PRUN) and pseudobaptigenin (PBAP). The compounds were measured as aglycones after enzymatic hydrolysis. A single intake of an amount of as low as 3·8 mg IRI (out of 38·8 mg IF in total) resulted in an IRI plasma concentration of 0·35 (sd 0·16) μm at 6.5 h post-ingestion. Compared to the plasma concentrations found for daidzein (0·39 μm) and genistein (0·06 μm), expected to be the main IF metabolites in plasma, the present findings indicate that IRI might possess a relatively high bioavailability. Furthermore, PRUN and PBAP were detected in human plasma for the first time.